Reversible mesophase in stress-annealed poly(3-hydroxybutyrate) fibers: A synchrotron x-ray and polarized ATR-FTIR study. (28th September 2021) - Perret, E.; Sharma, K.; Tritsch, S.; Hufenus, R.
Abstract: Structural changes in poly(3-hydroxybutyrate) (P3HB) monofilaments (diameter ~90 μm), induced by annealing under tensile stress (1 h with 1.6–40 MPa loading at 80–130 °C) have been investigated with synchrotron wide-angle x-ray diffraction (WAXD) and polarized attenuated total reflection Fourier transform infrared (ATR-FTIR) spectroscopy. Melt-spun P3HB fibers consist of an amorphous phase, a crystalline α-phase and a mesophase. Specific IR bands in s -polarized (electric field vector along the fiber axis) spectra have been identified to arise from the mesophase. For fibers annealed at low stress (1.6 MPa), the mesophase content practically disappears but can be recovered with tensile drawing. In-situ WAXD and polarized ATR-FTIR studies, performed during cyclic tensile loading/unloading, have revealed that the mesophase formation/dissolution is highly reversible in fibers annealed at low stress. This reversibility behavior, and the lack of off-axis reflections in WAXD patterns, support the theory that the mesophase is made of conformationally disordered and stretched chains, which are mainly located in-between α-crystals. Graphical abstract: Image 1 Highlights: Reversible mesophase formation during cyclic drawing of stress-annealed P3HB fibers. Mesophase in annealed P3HB fibers at low-stress (1.6 MPa) disappears and is recoverable through tensile drawing. In-situ polarized ATR-FTIR during cyclic drawing of P3HB fibers. In-situ synchrotron WAXD during cyclic drawing of P3HB fibers. Correlation of polarized ATR-FTIR results with WAXD results.